There seems to be a typo in the second equation you provided. It should be -7x + 9y = -47.
Now, we can solve the system of equations by elimination:
7x + 3y = -25
-7x + 9y = -47
Adding the two equations together:
(7x + 3y) + (-7x + 9y) = -25 + (-47)
7x - 7x + 3y + 9y = -25 - 47
12y = -72
y = -6
Now, substitute y = -6 into one of the equations:
7x + 3(-6) = -25
7x - 18 = -25
7x = -7
x = -1
Therefore, the solution to the system of equations is x = -1 and y = -6.
7x + 3y = -25
-7x * 9y = -47
1 answer